If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -12 = 3x(x + 2) Reorder the terms: -12 + 5x = 3x(x + 2) Reorder the terms: -12 + 5x = 3x(2 + x) -12 + 5x = (2 * 3x + x * 3x) -12 + 5x = (6x + 3x2) Solving -12 + 5x = 6x + 3x2 Solving for variable 'x'. Combine like terms: 5x + -6x = -1x -12 + -1x + -3x2 = 6x + 3x2 + -6x + -3x2 Reorder the terms: -12 + -1x + -3x2 = 6x + -6x + 3x2 + -3x2 Combine like terms: 6x + -6x = 0 -12 + -1x + -3x2 = 0 + 3x2 + -3x2 -12 + -1x + -3x2 = 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -12 + -1x + -3x2 = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(12 + x + 3x2) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(12 + x + 3x2)' equal to zero and attempt to solve: Simplifying 12 + x + 3x2 = 0 Solving 12 + x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 4 + 0.3333333333x + x2 = 0 Move the constant term to the right: Add '-4' to each side of the equation. 4 + 0.3333333333x + -4 + x2 = 0 + -4 Reorder the terms: 4 + -4 + 0.3333333333x + x2 = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 0.3333333333x + x2 = 0 + -4 0.3333333333x + x2 = 0 + -4 Combine like terms: 0 + -4 = -4 0.3333333333x + x2 = -4 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. 0.3333333333x + 0.25 + x2 = -4 + 0.25 Reorder the terms: 0.25 + 0.3333333333x + x2 = -4 + 0.25 Combine like terms: -4 + 0.25 = -3.75 0.25 + 0.3333333333x + x2 = -3.75 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = -3.75 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9-35x^2-4x^4=0 | | x^2-4x=-16 | | 46.50x=97138.5 | | 2x^3-7x^2-30x= | | 1414= | | -5(2f-7)+10f-30= | | 1414=0 | | 16-r*9=r | | 14n+-16n=18 | | 4y-15=25 | | -8(n-3)+2(n+1)= | | 165=11x+11 | | 6u-(2u+5)=2(u+1)-9 | | 7(y-5)/3=-3y | | 4-15x^2-4x^4=0 | | -3x=0.3 | | -10+-8n^2=-314 | | 12x^2+20-25= | | 18-4x=2x+10 | | f(x)=x^2+5x+12 | | f(x)=x^3+x | | -14c-7=21 | | 46500x=97138.5 | | -10-8n^2=314 | | 2x(2x)=39 | | 6v+-7v=-19 | | 4-3*Z=z-2 | | 46500x=97185.5 | | (2x-3)+15=2x-22 | | 9x^2+10=631 | | 2x+4=180 | | n*3-21=57 |